Prevalence and characteristics of children with mild intellectual disability in a French county. (10th June 2013) - David, M.; Dieterich, K.; Billette de Villemeur, A.; Jouk, P.‐S.; Counillon, J.; Larroque, B.; Bloch, J.; Cans, C.
Abstract Background Studies conducted on mild intellectual disability (MID) in children are infrequent and the prevalence rates vary widely. This study aimed to estimate the prevalence of MID in children in a French county (Isère), to describe the clinical signs and associated comorbidities, and to specify the aetiologies of this disability. Methods The target population was comprised of the 15 100 children born in 1997 residing in Isère County, France, in 2008. Our goal was to find the children in this group with MID diagnosed between 9 and 13 years of age. MID was defined as an overall IQ score of between 50 and 69 [International Statistical Classification of Diseases and Related Health Problems 10th Revision (ICD‐10)]; this definition was adjusted for the study by integrating confidence intervals so that the risk of IQ measurement relativity and possible discrepancy of scores could be taken into account. Children were identified through an administrative data source designed to assist disabled persons that contains health information, and an educational data source. Parents who agreed to let their children participate responded to an in‐depth questionnaire on their child's medical and academic history. A genetic investigation was proposed for those children whose MID had an unknown aetiology. Results The preliminary selection included 267 children, resulting in a prevalence rate of 18 per 1000 (CI [15.6; 19.9]), within the expected mean. Of these 267 cases, 181 families agreed to participate in the study (68%). MID more often affected boys [male gender ratio = 1.4 (CI [1.2; 1.6])], low socioeconomic groups, and families with a history of intellectual disability. The clinical signs and comorbidities associated with MID were very frequent, with 54% spoken language disorders and 10% pervasive developmental disorder. Only 9% of the children had undergone a genetic investigation before the study. The known aetiology rate for MID was 19% among all the children who had had genetic tests performed. Conclusion MID is an important public health issue based on its prevalence. The associated clinical signs and comorbidities may be warning signs of MID in case of learning difficulties. This study may help decision‐makers to develop and organise screening and care for MID.